2021
DOI: 10.3390/molecules26020515
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Selected Agri-Food Loss and Waste to Contribute to a Circular Economy: Applications in the Food, Cosmetic and Pharmaceutical Industries

Abstract: The food sector includes several large industries such as canned food, pasta, flour, frozen products, and beverages. Those industries transform agricultural raw materials into added-value products. The fruit and vegetable industry is the largest and fastest-growing segment of the world agricultural production market, which commercialize various products such as juices, jams, and dehydrated products, followed by the cereal industry products such as chocolate, beer, and vegetable oils are produced. Similarly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(129 citation statements)
references
References 282 publications
(267 reference statements)
0
106
0
Order By: Relevance
“…As it has been indicated in the introduction section, agricultural by-products have surged as an important source of bioactive compounds which bring about the possibility of valorization of these products to be applied in the food industry, for cosmetic, nutraceutical or pharmacological applications [28]. In this context, research has been done in order to develop suitable procedures to effectively extract the desired bioactive compounds from these sources.…”
Section: Valorization Of Agricultural By-products Using Dessmentioning
confidence: 99%
“…As it has been indicated in the introduction section, agricultural by-products have surged as an important source of bioactive compounds which bring about the possibility of valorization of these products to be applied in the food industry, for cosmetic, nutraceutical or pharmacological applications [28]. In this context, research has been done in order to develop suitable procedures to effectively extract the desired bioactive compounds from these sources.…”
Section: Valorization Of Agricultural By-products Using Dessmentioning
confidence: 99%
“…The by-products generated during the processing of fruit and vegetables are often discarded as waste despite being a rich source of bioactive compounds, including carotenoids [123]. The processing of fruit and vegetables in the United States and China results in approximately 15.0 and 32.0 million tons, respectively, of waste annually [124].…”
Section: Agri-food Waste-a Future Source For Dairy Fortification?mentioning
confidence: 99%
“…Recent studies showed that agro-food wastes must be considered renewable source of added-value bioactive compounds (BCs) [ 4 , 5 ]. The current linear economy model is based on the one acquired concepts from the industrial revolution, which implied a constant supply of products with a short life span, forcing an ever so increasing production to face the consumers’ needs [ 6 ]. This linear approach promotes the underexploitation of natural resources giving rise to a significant environmental and economic crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the proper management of this FLW will impact the change for a circular economy model and, a new concept perceived as an efficient option on the long run to transform and increment value to the FLW. BCs recovered from the food supply chain waste using sustainable extracting methodologies, will be used as raw material, or as new products, with health benefits creating industries with added value [ 6 ].…”
Section: Introductionmentioning
confidence: 99%